2019
DOI: 10.1101/871046
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Na2CO3-Responsive Photosynthetic and ROS Scavenging Mechanisms in Chloroplasts of Alkaligrass Revealed by Phosphoproteomics

Abstract: 4Alkali-salinity exerts severe osmotic, ionic and high-pH stresses to plants. To understand the 6 5 alkali-salinity responsive mechanisms underlying photosynthetic modulation and reactive 6 6 oxygen species (ROS) homeostasis, physiological and diverse quantitative proteomics 6 7 analyses of alkaligrass (Puccinellia tenuiflora) under Na 2 CO 3 stress were conducted. In 6 8 addition, Western blot, real-time PCR, and transgenic techniques were applied to validate the 6 9 proteomic results and test the functions o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 87 publications
4
5
0
Order By: Relevance
“…In the NaCl-stressed alkaligrass calli, the glycine betaine content was significantly increased. This result was consistent with the results from NaCl-stressed sugarcane calli [13] and the salinity-or alkali treated alkaligrass leaves [32,35,36].…”
Section: Diverse Osmotic Regulation Strategies In Salt-stressed Callussupporting
confidence: 91%
See 2 more Smart Citations
“…In the NaCl-stressed alkaligrass calli, the glycine betaine content was significantly increased. This result was consistent with the results from NaCl-stressed sugarcane calli [13] and the salinity-or alkali treated alkaligrass leaves [32,35,36].…”
Section: Diverse Osmotic Regulation Strategies In Salt-stressed Callussupporting
confidence: 91%
“…In the alkaligrass callus, the activities of APX, MDHAR and GR were NaCl-increased, but DHAR activity was NaCl-decreased. This result was similar to that in leaves under Na 2 CO 3 -treatmenf for 12h and 24h [35]. In addition, the amount of APX and an isoform of MDHAR, as well as the AsA content were all increased in the alkaligrass callus after salt stress.…”
Section: Salinity-responsive Ros Scavenging Pathways In Callussupporting
confidence: 82%
See 1 more Smart Citation
“…CAT pathway can directly dismutase H 2 O 2 to H 2 O and O 2 in peroxisomes. In salinity-/alkali-stressed alkaligrass, CAT activities were reduced in callus and short-term (12h and 24h) salt-treated leaves and roots [32,33], but induced in long-term (7 days) salt-treated leaves [30,31]. POD also catalyzes the reduction of H 2 O 2 using various substrates, such as phenolic compounds, lignin precursors, auxin and secondary metabolites.…”
Section: Salinity-responsive Ros Scavenging Pathways In Callusmentioning
confidence: 99%
“…Alkaligrass (Puccinellia tenuifora) is a monocotyledonous halophyte with high salinity and alkali tolerance. Our previous proteomics and physiological studies have reported the salt-/alkali-responsive mechanisms in leaves and roots in response to NaCl [30], Na 2 CO 3 [31][32][33], and NaHCO 3 [34] stresses.…”
Section: Introductionmentioning
confidence: 99%